Factors associated with patient´s preference in choosing their therapy for inflammatory bowel disease in Brazil - Wu, Adhan Amenomori [UNESP]; de BARROS, Jaqueline Ribeiro [UNESP]; Ramdeen, Madhoor; Baima, Julio Pinheiro [UNESP]; Saad-Hossne, Rogerio [UNESP]; Sassaki, Ligia Yukie [UNESP] (FapUNIFESP (SciELO), 2020)
Background – Biological therapy and new drugs have revolutionized the treatment of inflammatory bowel disease. Ideally, the choice of medication should be a shared decision with the patient, aiming at greater satisfaction, compliance, and consequently, favorable clinical outcome. Objective – This study aims to evaluate patient’s preferences in the choice of their therapy and the factors that influence this choice. Methods – This cross-sectional study enrolled 101 outpatients with Crohn’s disease or ulcerative colitis. The inclusion criteria were age ≥18 years and no previous exposure to biological therapy. Patients’ preferences were assessed through questions that addressed the preferred mode of administration (oral, subcutaneous, or intravenous) and the factors that determined the choice of medication (efficacy, medical indication, fear of medication, convenience, mode of application, and personal doctors’ indication). Results – The mean age was 43.6±13.5 years, 75.3% were female, and 81.2% were cases of ulcerative colitis. Regarding the mode of administration, the majority of patients preferred oral (87.1%), followed by intravenous (6.93%) and subcutaneous (5.94%) medications. The reasons were “I prefer to take it at home” (42.57%), “I have more freedom” (36.63%), “I don’t like self-application” (29.70%), and “I believe it works better” (19.80%). Younger patients and patients in clinical disease activity preferred intravenous mode compared to the oral route (P<0.05). Doctor’s opinion (98%) was an important factor associated with the medication choice. Conclusion – Oral route was the preferred mode of administration and most patients took their physician’s opinion into account in their choice of medication.
Fatores associados com a escolha da terapia nos pacientes com doença inflamatória intestinal no Brasil
Keywords: Biological therapy; Crohn disease; Drug administration routes; Inflammatory bowel diseases; Ulcerative colitis